Peran Badan Usaha Milik Desa Dalam Meningkatkan Ekonomi Masyarakat Perspektif Hukum Ekonomi Syari’ah - Musyarofah, Lailatul; Azizah, Ninik (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
Village-owned enterprises (BUMDes) aim to manage village assets and potential to improve community welfare. One of the business units managed is the Pandansili swimming pool, which is a tourist attraction and plays a role in improving the village economy. However, its management still faces challenges, such as limited professional human resources and lack of innovation. Therefore, a strategy is needed to strengthen human resources as well as the application of sharia economic principles that emphasize justice in wealth distribution. This research aims to: (1) to identify the role of BUMDes in improving the economy of the Ngampungan Village community, Bareng Subdistrict, Jombang Regency, and (2) to identify the role of BUMDes in improving the economy of the Ngampungan Village community, Bareng Subdistrict, Jombang Regency from the perspective of sharia economic law. This research uses an empirical juridical approach with a conceptual approach and applies inductive and descriptive methods. Data collection is done through observation, interviews, documents. The findings through interviews with the head of Ngampungan Village, Mr. Rohan, and the BUMDes administrator, Mr. Kusnadi, show that BUMDes plays an important role in improving the community's economy, especially through the management of Pandansili swimming pool tourism. Since joining in the management of tourism, the community has experienced economic improvement, both as employees, traders, and parking attendants. Initially, around 10% of the community was classified as economically weak, but since the tourism, this figure has decreased by around 4%. The application of sharia economic principles, such as fairness in wealth distribution and transparency in profit sharing, allows the community to actively participate in tourism management, thereby improving the welfare of Ngampungan Village